Inclusive Net-Zero Framework for Assessing Urban Transport Policies and Programmes—Case of India - Mahadevia, Darshini; Lathia, Saumya; Munshi, Talat (Transportation Development Research, 2026)
India’s Net-Zero commitment, announced at the COP26 held in Glasgow, underscores the critical role of urban transport in achieving long-term climate goals. This paper examines the adequacy of existing transport policies and programmes at both macro (national and state) and city levels in advancing Net-Zero readiness. This paper critiques the conventional Avoid–Shift–Improve framework and introduces the ERASI framework (Enhance, Retain, Avoid, Shift, Improve) as a more contextually relevant paradigm for Indian cities and the Global South. It then, through a systematic assessment of the policy documents at all the levels, identifies structural gaps, fragmented approaches, and misalignments across governance scales. The papers findings highlight that Indian cities possess a comparatively sustainable urban form, yet policies inadequately support integrated planning to sustain compact, mixed-use development, under-scoring the need for ‘Retain’ principles through coherent long-term strategies. Indian cities also record low mobility of specific populations, which requires the ‘Enhance’ option. The paper also highlights the absence of coherent strategies linking macro and local interventions, insufficient integration of inclusivity and transport justice, and the need for alignment between technological transitions and governance mechanisms. The paper also argues that achieving Net-Zero transport requires a reframing of urban transport policy that emphasizes equity, and coherence in existing frameworks.